Risiko Investasi pada Inovasi Teknologi Ramah Lingkungan dalam Pengolahan Limbah Plastik - Rusmina, Cut; Zainuddin, Zainuddin; Juwita, Juwita; Marlina, Marlina; Jelita, Adriani (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Investing in green technologies for plastic waste processing presents both strategic opportunities and complex risk challenges. This study uses a literature review approach to identify, analyze, and classify the key risks associated with green investment projects in the plastics recycling sector, including technological, market, regulatory, and financial risks. Through analytical reviews of reports and studies based on impact matrix models, technological risk is found to be the most dominant, followed by market and regulatory risks. The study also highlights the importance of collaboration among industry players, investors, research institutions, and government agencies in formulating adaptive and systematic risk mitigation strategies. Suggested policy recommendations include regulatory alignment, fiscal incentives, and technical capacity building. With a structured risk management approach, investments in green technologies are expected to contribute significantly to the development of a sustainable circular economy in Indonesia.